2013
DOI: 10.3126/nepjoph.v5i1.7832
|View full text |Cite
|
Sign up to set email alerts
|

Results of the Bhaktapur Glaucoma Study, Nepal

Abstract: I nt r oduction: The Bhaktapur Glaucoma Study is a population-based, cross-sectional and longitudinal study undertaken in one of the districts of Nepal. Objectives: To determine the prevalence of glaucoma in Bhaktapur district, Nepal. Materials and methods: Thirty clusters were randomly selected and a door-to-door census was conducted to identify citizens 40 years of age and older. Four thousand eight hundred individuals fulfilling the eligibility criteria were referred to the base hospital in Kathmandu for a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 61 publications
7
4
0
Order By: Relevance
“…In this study, we found the majority of pa ents having POAG which is similar to other studies conducted in Nepal and [8][9][10][11][12][13] other south Asian countries. The study by Dr. Sah R. P. et al was a community based cross sec onal study done in 1600 10 pa ents above 40 years in Sunsari district of Nepal .…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In this study, we found the majority of pa ents having POAG which is similar to other studies conducted in Nepal and [8][9][10][11][12][13] other south Asian countries. The study by Dr. Sah R. P. et al was a community based cross sec onal study done in 1600 10 pa ents above 40 years in Sunsari district of Nepal .…”
Section: Discussionsupporting
confidence: 89%
“…In Bhaktapur study conducted by Suman S Thapa et al reported POAG (1.245 %) being the highest among types of glaucoma which is similar to ours 12 having 1.78% However we didn't find any cases of PACG in our study. In another study by Suman S Thapa et al showed that approximately 2 to 4% of pa ents 50 years or older were 13 newly diagnosed with P0AG . Early detec on and treatment is necessary for reduc on of blindness due to glaucoma.…”
Section: Discussionmentioning
confidence: 98%
“…In this study we found that there was an increase in the prevalence of glaucoma with the increasing age.The mean age at which glaucoma was diagnosed was 55.29 years. The results of our study are comparable to the results of Bhaktapur glaucoma study (Thapa SS et al 2013).…”
Section: Discussionsupporting
confidence: 89%
“…In this study the mean vertical cup disc ratio in the glaucoma diagnosis group was 0.69 compared to 0.56 which is similar to the results of Bhaktapur glaucoma study which states that the VCDR above 0.6 should be looked into with suspicion (Thapa SS et al 2013).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation